Poethics? The Use of Biblical Hebrew Poetry in Ethical Reflection on the Old Testament - Boda, Mark J. 1962- (2015)
This study traces the history of scholarship in the discipline of Old Testament ethics in the Anglo-American tradition over the past century, focusing on the use of poetry and poetic texts throughout this period. It identifies James Muilenburg as a key figure who paved the way for greater sensitivity to the role that Hebrew poetic texts can play within ethical reflection, not merely in terms of their ethical themes, but more importantly, in terms of their poetic form.
Keywords: Bible. Old Testament; biblical Hebrew poetry; Ethics; Hebrew Bible; Hebrew literature; Imagination; Law; literary method; Metaphor; Morality; Narrative; Old Testament; Poetics; Poetry; Prophets; Psalms; Wisdom Literature